TAREKAT DAN POLITIK: Studi Living Sufism Tarekat Hizib Nahdlatul Wathan - M Rohman Ziadi (Living Islam: Journal of Islamic Discourses, 2018)
Tarekat (Tariqa) is a Sufi brotherhood that contains and practices sufistic principles. In Sufism, there is a distinc- tive concept, namely zuhud. Zuhud is the emptiness of the desire for something, which means limiting the desire to get something worldly or pleasure (profane). At this point, it can be seen that in the Sufistic tradition it should be to avoid the desire for something profane, including politics. However, Tarekat Hizib Nahdlatul Wathan as a tarekat appeared to be actively involved in politics, even the founder and murshid of the Tarekat Hizib Nahdlatul Wathan became the main figure in politics in Lombok. This is important to note, because on the one hand the Tarekat Hizib Nahdlatul Wathan is a tarekat but on the other hand it appears to be actively involved in politics. Therefore, the authors are interested in discussing more about the Tarekat Hizib Nahdlatul Wathan and its con- tribution to politics in Lombok. This article will explain the study of living sufism of the Tarekat Hizib Nahdlatul Wathan.